PENGARUH STRATEGI PEMASARAN DENGAN KONSEP AIDA (ATTENTION, INTEREST, DESIRE, ACTION) TERHADAP RESPON NASABAH MENGAMBANG PADA BANK SYARIAH (STUDI PADA BANK SYARIAH DI WILAYAH CIBADAK-SUKABUMI) (Equilibrium: Jurnal Ekonomi Syariah, 2019)
This study aims to determine the effect of marketing strategies with the AIDA concept on the response of customers floating on Islamic banks. The research method uses a quantitative approach with Logistic Regression analysis techniques. The technique of collecting data uses a questionnaire technique distributed to sharia bank customers in the Cibadak area that has accounts with conventional banks, the number of respondents taken as many as 60 respondents using non probability sampling method that is by convenience sampling. The results of this study indicate that there is no partial significant influence between the variables of attention, interest, desire, action on the variable response of floating customers